تأثير إضافة مولاس الشوندر السكري عند مستويات مختلفة من الشد الرطوبي في نمو وإنتاجية نبات البندورة - إبراهيم, جهاد; سمرة, بديع; كردي, علا (Latakia University Journal -Biological Sciences Series, 2019)
من خلال دراسة تأثير إضافة مستويات مختلفة من مولاس الشوندر السكري (-50-0 100-150ل/هكتار) عند مستويات مختلفة من الشد الرطوبي (800-600-400 ميلي بار ) في نمو وإنتاجية نبات البندورة في تربة سلتية لومية مأخوذة من مركز البحوث العلمية الزراعية (ستخيرس) والمنفذة ضمن بيت بلاستيكي صغير في جامعة تشرين خلال العام 2017-2016. تبين أن مساحة المسطح الورقي تتراوح بين 0.931m2إلى 2.39 m2للنبات الواحد بعد ثلاثة أشهر من الزراعة وكانت أفضل مساحة عند مستوى إضافة 100ل/هكتار ونسبة شد رطوبي 600ميلي بار. تبين أنه مع زيادة نسبة الإضافة من المولاس عند نفس الشد الرطوبي تزداد نسبة العقد في الثمار عند جميع مستويات الشد الرطوبي وبلغ قيمة 70.02%عند شد رطوبي 400ميلي بار ومستوى إضافة من المولاس 150 ل/هكتار مقارنة بمعاملة الشاهد بدون إضافة المولاس حيث بلغ قيمة 43.85% وعند مستوى إضافة 150ل/هكتار من المولاس ,تنخفض نسبة العقد مع زيادة الشد الرطوبي بشكل واضح. كانت إنتاجية النبات الواحد أعلى مايمكن عند مستوى إضافة 150ل/هكتار من المولاس وشد رطوبي 400ميلي بار(قريب من السعة الحقلية) حيث بلغت 4682غ/نبات. Through a study conducted to find out the effect of adding different levels of sugar beet molasses(0-50-100-150L/h) at different levels of moisture tension(400-600-800Milli Bar) in the properties of physical soil and on the growth and productivity of tomato plant in Celtic and Lome soil taken from the center for Agricultural Scientific Research (Stkires) and implemented within a small plastic house in Tishreen University during the year2016-2017. After three months of agriculture, the area of the paper surface ranges from 0.931m2 to 2.39 m2per plant, It was found that with the increase in the level of addition,The surface area of paper was as large as possible at the level of addition of molasses 100L/h and moisture tension 600 Milli Bar. It was found that with the increase in the percentage of addition of molasses at the same moisture tension, the proportion of the contract in the fruits at all levels of moisture tension increases and values70.02%at moisture tension 400 Milli Bar and the level of addition of molasses 150 L/h,Compared to the treatment without adding molasses , Where the values reached 43.85% and at the added level of molasses150L/h The proportion of the contract decreases with the increase of moisture tension clearly. The productiving of each plant was as large as possible at the level of addition of molasses 150L/h and moisture tension 400 Milli Bar(about 85% of the field capacity)where it reached 4682g/plant.